Teaching students to identify and address significant critical moments in cross-cultural social work practice. - Lee, Eunjung; Kourgiantakis, Toula (Social Work Education, 2024)
Critical social work practice should transcend across micro, mezzo, and macro levels, and it is a social work educator's responsibility to foster skills that are contextualized and connected to social justice and anti-oppressive frameworks. Despite the importance of addressing and integrating systemic oppression in cross-cultural social work practice, students struggle with being able to translate their knowing into doing. Using a video case of a client named Glen who is receiving services in an outpatient addiction counseling program, we discuss how to incorporate a critical, systemic, and structural lens in social work mental health practice. Psychotherapy process research cautions against weighing an entire session equally and underlines the importance of examining critical moments within the session. Guided by a psychotherapy process research approach, we illustrate how we train students to identify significant in-session moments and encourage students to brainstorm and practice in-session social work tasks that integrate a structural lens with clinical interventions. This teaching approach also illustrates how to translate critical scholarship and approaches into micro-level teachable moments in classroom to guide students' cross-cultural practice. The pedagogical approach using a micro-analysis of in-session social work tasks heightens students' awareness and competence in how to intervene with culturally diverse clients.